Search for Higgs boson decays into a pair of pseudoscalar particles in the bbμμ final state with the ATLAS detector in pp collisions at √s=13 TeV - Aad, Georges; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Physical review, 2022)
This paper presents a search for decays of the Higgs boson with a mass of 125 GeV into a pair of new pseudoscalar particles, H→aa, where one a-boson decays into a b-quark pair and the other into a muon pair. The search uses 139 fb−1 of proton-proton collision data at a center-of-mass energy of √s=13 TeV recorded between 2015 and 2018 by the ATLAS experiment at the LHC. A narrow dimuon resonance is searched for in the invariant mass spectrum between 16 GeV and 62 GeV. The largest excess of events above the Standard Model backgrounds is observed at a dimuon invariant mass of 52 GeV and corresponds to a local (global) significance of 3.3σ (1.7σ). Upper limits at 95% confidence level are placed on the branching ratio of the Higgs boson to the bbμμ final state, B(H→aa→bbμμ), and are in the range 0.2-4.0×10−4, depending on the signal mass hypothesis.